Benthic Dissolved Silicon and Iron Cycling at Glaciated Patagonian Fjord Heads. Issue 11 (25th November 2022) - Ng, Hong Chin; Hawkings, Jon R.; Bertrand, Sebastien; Summers, Brent A.; Sieber, Matthias; Conway, Tim M.; Freitas, Felipe S.; Ward, James P. J.; Pryer, Helena V.; Wadham, Jemma L.; Arndt, Sandra; Hendry, Katharine R.
Abstract: Glacier meltwater supplies silicon (Si) and iron (Fe) sourced from weathered bedrock to downstream ecosystems. However, the extent to which these nutrients reach the ocean is regulated by the nature of the benthic cycling of dissolved Si and Fe within fjord systems, given the rapid deposition of reactive particulate fractions at fjord heads. Here, we examine the benthic cycling of the two nutrients at four Patagonian fjord heads through geochemical analyses of sediment pore waters, including Si and Fe isotopes (δ 30 Si and δ 56 Fe), and reaction‐transport modeling for Si. A high diffusive flux of dissolved Fe from the fjord sediments (up to 0.02 mmol m −2  day −1 ) compared to open ocean sediments (typically <0.001 mmol m −2  day −1 ) is supported by both reductive and non‐reductive dissolution of glacially‐sourced reactive Fe phases, as reflected by the range of pore water δ 56 Fe (−2.7 to +0.8‰). In contrast, the diffusive flux of dissolved Si from the fjord sediments (0.02–0.05 mmol m −2  day −1 ) is relatively low (typical ocean values are >0.1 mmol m −2  day −1 ). High pore water δ 30 Si (up to +3.3‰) observed near the Fe(II)‐Fe(III) redox boundary is likely associated with the removal of dissolved Si by Fe(III) mineral phases, which, together with high sedimentation rates, contribute to the low diffusive flux of Si at the sampled sites. Our results suggest that early diagenesis promotes the release of dissolved Fe, yet suppresses the release of dissolved Si at glaciated fjord heads, which has significant implications for understanding the downstream transport of these nutrients along fjord systems. Plain Language Summary: Through physical grinding and chemical reactions, glaciers are capable of releasing nutrients such as silicon and iron from the underlying rocks. In particular, there is a growing interest in the supply of these glacier‐sourced nutrients to sustain the growth of marine life in high‐latitude estuaries (fjords) and the adjacent coastal ocean. However, a substantial portion of the glacier‐sourced nutrients may be removed by rapid settling of debris (sediments) at the heads of these fjords, before they can be used by marine life. This study analyzes the chemistry of fluids within sediments collected from Patagonian fjord near river and glacial inputs to investigate the fate of glacier‐sourced nutrients (silicon and iron) that have been transferred to the fjord floor. Our laboratory analysis and calculations reveal that biological, chemical and geological processes in these sediments release significant amounts of iron back into the overlying fjord waters, but these high levels of iron chemically bind silicon, restricting its release into fjord waters. The disproportionate release of the two nutrients from fjord sediments found in this study advances our understanding of the modes of supply of glacier‐sourced nutrients to fjords and the coastal ocean. Abstract : Schematic shows the coupling of benthic Fe and Si cycling, and the inferred spatial difference in the supply of easily reducible Fe (oxy‐)hydroxides and the intensity of pore water advection between the fjord sites. Adsorption of Si onto Fe (oxy‐)hydroxides and co‐precipitation of amorphous Fe‐Si phases occur under relatively oxic conditions in the upper sediments, while Si is released back to solution following the reductive dissolution of Fe in the ferruginous zone. Circles with brighter colors and solid outlines represent solid‐bound Si and Fe(III) phases, while circles with lighter colors and dashed outlines represent dissolved Si and Fe 2+ phases.